Pengaruh Akuntabilitas dan Transparansi Dana Desa Terhadap Kinerja Pemerintah - ardiansyah, M. faizin; Umaimah, Umaimah (Jurnal Akuntansi UMMI, 2023)
The purpose of this study was to examine the effect of accountability and transparency on government performance. The grand theory in this study is the theory of stawarnership which explains the existence of local government as one of the institutions that can be trusted in acting in accordance with its duties and functions that prioritize and prioritize the public interest, provide financial responsibility, so that economic goals, public services and public welfare can be achieved. This study tested the hypothesis by taking samples from Roomo village government employees and Sukamulyo village government employees. The results of the hypothesis test obtained empirical findings that accountability and transparency affect the performance of village government.